Self-Concept of Adolescent Girls with Toxic Parents - Rezky Winanda; Rohmah Rifani; Dian Novita Siswanti (Program Studi Bimbingan dan Konseling, Fakultas Ilmu Pendidikan, Universitas Negeri Medan, 2022)
Toxic parental behavior has various negative impacts on adolescents in the identity search phase. This study focuses on knowing the form of negative behavior that adolescents get from toxic parents, self-concept, and the meaning of parent-child relationships for adolescents. This study uses a qualitative method using phenomenological interpretive analysis. The research respondents were women aged 19 and 21 years who lived with their parents as many as three people—data collection techniques using questionnaires and semi-structured interviews. The results of data analysis showed that there were six forms of toxic parental behavior obtained by adolescents girls: neglect, physical and verbal violence, anger venting, controlling, and differences in treatment with siblings. Harmful parental behavior has an impact on adolescent girls self-concept. The formed self-concept is positive and negative. Positive self-concept based on self-knowledge and self-expectations of adolescents. Self-concept based on adolescent negative self-assessment.. Adolescent girls interpret the relationship between parents and children with views about parents, family, and and the concept of ideal parent-child relationship.